Os assistentes sociais e o CRAS : carreiras, conflitos e atuação profissional em Aracaju - Lemos, Francilaine dos Santos (2016)
This thesis aims to analyze the careers, conflict and professional practice of social workers who work in Social Assistance Reference Centers - CRAS Aracaju. With regard specifically to social workers who participate in professional actions for vulnerable groups, which will later be classified as individuals at risk and social vulnerability, which are attended these social service centers. To realize this goal, we need to understand the social and historical conditions that made possible the emergence of this profession in Brazil, as well as analyze the inclusion of these professionals in the construction of public affairs and public policy, which shows a concern with the social condition of these individuals who are in a situation of risk and social vulnerability. You need to identify too, as these professionals organized around this issue, and later in these policies. As they have been entered in these social service centers, which their social and professional purpose, what is the position of these professionals facing the development of public policies for actors who have in its history a large number of social deficits, as is the exemplary case of children and adolescents classified at risk or social vulnerability, as there are elderly, disabled, and other groups that may need support care for face even occasionally, some kind of social risk. Therefore, I will analyze social workers who present themselves as professionals who fight for social causes, as I will analyze the social representations that these professionals have of themselves and the social world of which they are part, and trying to understand how to establish and how to maintain the relationship between professional and public policy. What are the dilemmas and conflicts faced by these professionals in their respective workplaces, which are public policy operators, but are also a kind of government tax, tax those that carry as a professional and social cause the guarantee of social welfare, promotion of social rights and the inviolability of social rights, guaranteed by the State and monitored by the social worker.